A Study on the Balance Between Work and Family of Nepali Army Officers - Koirala, Laxmi Bilas (Unity Journal, 2021)
This study tries to explore and examine the relationships of work-family balance among army officers of the Nepal Army. The objectives of the study is to discover the issues and consequences of the work family confl ict by examining and discussing the impact of time, stress and job satisfaction on work-family relation and to suggest some recommendations to maintain the balance between the two. This study is simply base on desk review of research papers and information on work-family relation of army officers. Unprecedented problems of work family conflict are a common phenomenon within modern organizations. Stress, low performance, absenteeism, quitting from the force and committing suicide are the consequences of the work-family conflict So, the organizations are compelled to manage all causes of conflict before escalating the adverse effects. The study has followed a step-by-step approach to undertake review of the research papers. The results of this study reveal that work-life conflict and stress have a significant positive relationship. The findings of the study will encourage the Nepal Army for further research on work family balance and the additional examination may provide better understanding of truth. It is also hope that the results and recommendations gleaned from this study may assist the Nepal Army in making policies and programs related to work family conflict in future. Should the Nepal Army leadership fail to work proactively to ensure this balance, this may provide ground for a new kind of conflict.